The philosophy of Husserl - Hopkins, Burt C. (Continental European philosophy., 2011)
"As the founder of phenomenology, Edmund Husserl has been hugely influential in the development of contemporary continental philosophy. In The Philosophy of Husserl, Burt Hopkins shows that the unity of Husserl's philosophical enterprise is found in its investigation of the origins of cognition, being, meaning, and ultimately philosophy itself. Hopkins challenges the prevailing view that Husserl's late turn to history is inconsistent with his earlier attempts to establish phenomenology as a pure science and also the view of Heidegger and Derrida, that the limits of transcendental phenomenology are historically driven by ancient Greek philosophy. Part 1 presents Plato's written and unwritten theories of eidē and Aristotle's criticism of both. Part 2 traces Husserl's early investigations into the formation of mathematical and logical concepts and charts the critical necessity that leads from descriptive psychology to transcendentally pure phenomenology. Part 3 investigates the movement of Husserl's phenomenology of transcendental consciousness to that of monadological intersubjectivity. Part 4 presents the final stage of the development of Husserl's thought, which situates monadological intersubjectivity within the context of the historical a priori constituitive of all meaning. Part 5 exposes the unwarranted historical presuppositions that guide Heidegger's fundamental ontological and Derrida's deconstructive criticisms of Husserl's transcendental phenomenology"--Publisher description, p. [4] of cover.